Predicting structural behaviour of pressure vessels using large scale meta-modelling applied to plug type heat exchanger header boxes - Beyers, Wilhelm Andre (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.